PROBLEMATIKA USE OF ONLINE MEDIA AS A LEARNING SOLUTION DURING THE COVID-19 PANDEMIC - Innayatul Laili (Jurnal Scientia, 2022)
This research aims to find out the problems that occur in the implementation of online learning in the midst of the covid-19 pandemic. The object of the study was a student of State High School 1 Pasuruan. Research with descriptive qualitative approach design is used in this research. It is expected that by using this approach the problems that occur on the ground can be interpreted and described very clearly and easily understood. The results of this study are known that the most widely used application in online learning is google classroom, followed by the use of google form, whattshap, and youtube applications. In its implementation the use of these various applications has obstacles including 1) difficulty in operating a laptop or mobile phone; 2) lack of internet data packets and does not have wifi network; and 3) Weak internet signal. These obstacles can be overcome with several solutions including the addition of internet quotas for students and training in the operation of online learning media that can be done with the help of local governments. The conclusion obtained from the results of this study is the importance of the role of the government in overcoming online learning obstacles in the field. In addition, the facilitation provided by the central government must also be seen its effectiveness whether it can be fulfilled or vice versa. Keywords: Learning, learning media, online, mobile phones.